How to Improve Indonesian Language Learning Outcomes at Madrasah Tsanawiyah Through the Talking Stick Learning Model - Firman Firman; Mirnawati Mirnawati; Nurul Aswar (Universitas Teknokrat Indonesia, 2021)
This research is classroom action research because it relates to efforts to improve learning practices in the classroom. The data collection technique used in this research is multi-technique or multi-instrument, namely: observation, measurement, and documentation. The data analysis technique used is descriptive quantitative analysis. The data obtained in the form of learning outcomes and activity observations were processed using descriptive quantitative analysis but first scoring and tabulated, then the frequency and percentage were calculated to be a reference in conducting descriptions. The results showed that; (1) The value of student learning outcomes class VII MTs Negeri Palopo in the first cycle of 20 students, there are ten students or 50% who meet the minimum completeness criteria, whereas in cycle II it increased from 20 students there were 16 students or 80% who met the minimum completeness criteria; (2) Thus, the action hypothesis proposed in this study is proof that if the talking stick model of learning is applied, the learning outcomes of the Indonesian language studies for grade VII students of MTs Negeri Palopo will increase.